2014
DOI: 10.15578/iaj.9.2.2014.155-164
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Use of Different Rica Probiotic Bacteria on Survival Rate and Production of Cultured Tiger Shrimp in Semi-Intensive Ponds

Abstract: Tiger shrimp diseases have occured in Indonesian shrimp ponds for more than two decades. In order to overcome this problem, five types of the RICA probiotic bacteria were tested in nine 250 m2 semi-intensive ponds of the Research and Development Institute for Coastal Aquaculture Marana Station. In the present study three different alternate use of the RICA probiotics were tested for tiger shrimp culture incompletely randomized design experiment. There were three treatments here namely: A) alternate use of prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…When TBV/TPC ratio is increase more than 10%, some pathogenic Vibrio spp. might be harmful to the shrimp (Atmomarsono & Nurbaya, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When TBV/TPC ratio is increase more than 10%, some pathogenic Vibrio spp. might be harmful to the shrimp (Atmomarsono & Nurbaya, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Actually TBV in the control shrimp pond water did not increase much, but TBV/TPC ratio increased to 17.48% since TPC in the control shrimp pond water decreased. Atmomarsono & Nurbaya (2014) also reported that percentage of TBV/TPC ratio in the shrimp pond water over than 10% was dangerous for the cultured shrimp.…”
Section: Survival Rate and Productionmentioning
confidence: 98%
See 1 more Smart Citation
“…One way to solve this problem is using probiotic to prevent shrimp diseases (Poernomo, 2004;Waston et al, 2008). The main culprit of shrimp diseases is vibriosis caused by Vibrio harveyi which could wipe out 100% of the cultured shrimp (Flegel, 2012;Atmomarsono & Nurbaya, 2014). As an opportunistic pathogen, Vibrio harveyi will only become pathogenic bacteria causing shrimp diseases when the pond water quality is poor (Atmomarsono & Susianingsih, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotic bacteria are non-pathogenic bacteria usually used to protect the shrimp from pathogenic microorganisms, inhibit the growth of pathogenic bacteria, neutralize poor pond water quality such as organic matter, H 2 S, NH 3 -N, and NO 2 -N, and function as food (Poernomo, 2004;Wang et al, 2008). Probiotic bacteria can be isolated from sea sediment, pond sediment, mangrove leaves, and macroalgae (Atmomarsono et al, 2009;Susianingsih et al, 2012;Tampangallo et al, 2013;Atmomarsono & Nurbaya, 2014). There are various types of domestically produced and imported probiotics available in the market.…”
Section: Introductionmentioning
confidence: 99%